Pengembangan Kesehatan Tanah Berbasis Zeolit: Strategi Perbaikan Sifat Kimia Tanah Secara Berkelanjutan - Mulyani, Oviyanti; Sudirja, Rija; Solihin, Eso; Sara, Dirga Sapta; Husein, Anne Yuliana (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
These chemical residues affect the natural balance of soil biota, leading to a decrease in soil pH, areduction in Cation Exchange Capacity (CEC), and a general decline in land productivity. If not treatedpromptly, this damage could harm health and food sustainability. The application of eco-friendlyproducts in modifying soil characteristics, including high-quality zeolite, remains common today. Thisstudy aims to examine the effects of zeolite application on the dynamics of soil chemical characteristicsto promote the development of a sustainable agricultural system. This study employed a RandomizedBlock Design (RBD) containing six different treatments such as five varying recommendation dosagesof zeolite (0.5, 1, 1.5, 2, and 2.5) and one control treatment devoid of zeolite for comparative analysis.Each treatment was reproduced three times, yielding a total of eighteen experimental plots. Soilchemical parameters (pH and CEC) are the primary focus of this experiment. The study's resultsindicated that during the last weeks of testing, applying 1.5 to 2 doses of zeolite proved to be the mostbeneficial, as it continuously raised the pH and CEC levels. Both Pearson and Spearman tests indicatethat the correlation between variables improves from first week to week fourth week. This suggeststhat the effects of the treatment, possibly zeolite application or an alternative treatment, start afterseveral weeks. The results of this investigation indicate that incubation time in zeolite applicationimportant for exhibits effective buffering properties and functions efficiently, significantly improvingthe chemical properties in soil.